SCHOOLING OF UKRAINIAN PUPILS IN VIENNA IN CONDITIONS OF FORCED MIGRATION - Vasylchenko, Olena (Studies in Comparative Education, 2024)
The article deals with the problem of the integration of Ukrainian pupils into the Austrian school system in the context of forced migration. The aim of the paper is to establish the relationship between the traumatic experience of war, displacement and the quality of learning in new conditions, as well as delineate the factors that influence the reduction of stress in the classroom and, as a result, improve learning and integration in a new community. The vast majority of children was accepted by Vienna where there were taken various measures to ensure that Ukrainian children could be integrated into the learning process in the Austrian school system. There are a lot of different factors that play an important role in the process of this integration. In order to determine these factors, interviews were conducted with mothers and data were collected, analyzed and conclusions were drawn. It has been found that there were different stories of the integration into a new community even within one family. It depended on the atmosphere in the classroom, a variety of materials and forms of work, empathy of the teacher and classmates, acceptance of the school as the safe place etc.